ISO 9000 and Accrediation-A Comparative Study - Garde, Raghvendra (Journal of Engineering Education Transformations, 2000)
The eighties and the nineties can be truly called the quality decades. Especially the nineties. When in 1987, the International Organization for Standardization (ISO) brought out Quality Assurance System Standards under the generic ISO 9000 series, the quality movement really got going.